INFLUENCE OF VITAMINS ON GROWTH AND DEVELOPMENT OF MYCELIUM OF SOME BASIDIOMYCETES IN LIQUID MEDIUM - Minakov D.V. (Техника и технология пищевых производств, 2016)
The relevance of the research is to study the need for new strains of edible mushrooms for accumulation of mycelia biomass which would create the optimum physiological culture conditions to achieve high and stable yield of biomass. One way to increase the yield of high quality mycelium can be administering vitamins at different stages of fungi ontogenesis. The aim of the research was to study the effect of vitamins on growth and development of the mycelium of Armillaria mellea (Vahl: Fr.) P. Kumm and Lentinula edodes (Berk.) Pegler F-1000 when cultured under stationary conditions. The biomass of the mycelium has been obtained on a liquid nutrient medium composed of 1.0% of glucose, 0.5% of peptone main dry, 1.1% of KHPO, 0.1% of MgSO ? 7HO, 97.3% of HO (dist.). To study the effect of vitamins on the growth of mycelium of fungi cultures of A. mellea and L. edodes we used riboflavin (LSR-002944/07), thiamine (LSR-002679/07), nicotinic acid (LSR-015076/01), vitamin C (LSR-000781/08) and a mixture of four vitamins in a glucose-peptone medium at concentrations of 0.15, 0.20, 0.40, 0.60 and 0.80 mg/ml. As a result, comparing the data obtained on the control and fortified media, both positive and negative effects of adding vitamins on the growth rate and the development of A. mellea mycelium and L. edodes have been established. The kinetic and condition-growing indices of mycelium A. mellea and L. edodes have been found. It has been stated that riboflavin and thiamine have a stimulating effect on the intensification of mycelium growing processes in A. mellea and L. edodes . Using these vitamins in optimum concentration of 0.20 mg/ml allows increasing the average daily rate of growth of mycelium A. mellea vs. a control one in 1.44-1.46 times. Nicotinic acid and vitamin C demonstrate low stimulating efficiency on the growth of A. mellea and L. edodes.